Wogonin Alleviates Cisplatin-induced Cardiotoxicity in Mice Via Inhibiting Gasdermin D-mediated Pyroptosis. Issue 4 (October 2021) - Xu, Jiajun; Zhang, Bin; Chu, Zhenliang; Jiang, Fenfen; Han, Jibo
Abstract : Abstract: Cardiotoxicity has been well documented as a side effect of cisplatin (CDDP) treatment. The inflammatory response plays a crucial role in the pathological process of CDDP-induced cardiotoxicity. Wogonin is a natural flavonoid compound that possesses cardioprotective and anti-inflammatory qualities. Knowledge of the pharmacological effect and mechanism of wogonin could reveal an efficient way to identify therapeutic strategies. In this study, the potential of wogonin to antagonize CDDP-induced cardiotoxicity was evaluated in C57BL/6 mice in vivo and in H9c2 cells in vitro. The results showed that wogonin protected against CDDP-induced cardiac dysfunction, myocardial injury, and pyroptosis in vivo. Using a Gasdermin D expression plasmid, we revealed that wogonin dramatically reduced CDDP-induced pyroptosis by modulating the Gasdermin D protein in H9c2 cells. In conclusion, wogonin has great potential in attenuating CDDP-induced cardiotoxicity. In addition, greater emphasis should be placed on the antipyroptotic effects of wogonin for the treatment of other diseases.